INTERACTION IN AN EDUCATIONAL ENVIRONMENT WITH VIRTUAL AND AUGMENTED REALITY - Svitlana H. Lytvynova; Natalia V. Soroko (Інформаційні технології і засоби навчання)
The article is devoted to the problem and features of the use of virtual and augmented reality at general school. The integration of virtual reality (VR) and augmented reality (AR) in educational environment has opened up new possibilities for engaging and immersive learning experiences. This paper aims to explore the features of participants' interaction within an educational context using VR and AR technologies. To achieve the purpose of our study and also to clarify the problem of determining the features of interaction models of participants in the educational process of a general education institution using virtual and augmented reality we used the following methods: systematic and comparative analysis of pedagogical, psychological, philosophical and sociological works, methodological and specialized literature; analysis of the pedagogical experience of using virtual and augmented reality in general school; synthesis and generalization to formulate the main points of the study; interpretation of the research results. A research study was conducted in a general educational institution, where an educational project using virtual and augmented reality was developed and implemented. The purpose of the project was to investigate the issues surrounding the interaction among participants in the educational process when utilizing these technologies. The results of the questionnaire showed the following: the participants' interaction in the educational process with the use of VR needs improvement, methodological recommendations and research on the organization of this environment for various purposes, such as, for example, students' research of new educational material, performance of laboratory work, joint work of students on research, instructions for the teacher's activities in working with students in VR, etc.; the participants’ interaction in the educational process with the use of AR is best understood by teachers and students, they use both ready-made AR technologies and personally created ones. We concluded that the use of virtual and augmented reality technologies in the educational process provides a wealth of teaching and learning resources that can enhance the learning experience and free participants from limitations in time and space. However, the effective organization of interaction between participants in the educational process using VR and AR requires careful consideration of educational space and pedagogical and methodological recommendations.